2003
DOI: 10.1016/s0899-3467(07)60051-2
|View full text |Cite
|
Sign up to set email alerts
|

Intra-instrument reliability of 4 goniometers

Abstract: Since the devices could measure reliably, whether expensive or more cost effective for students they would likely make adequate devices for training students on the methods for measuring ROM. There is previous data to suggest that older populations have gender differences and age differences with ROM. This study could not measure that and would make a useful follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…a) The sagittal head angle indicates the position of the head relative to the neck [ 28 ]. This angle is commonly affected by computer usage [ 17 ]. McEvoy and Grimmer (2006) reported that a decrease in this angle reflects a "poking-chin" posture [ 28 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…a) The sagittal head angle indicates the position of the head relative to the neck [ 28 ]. This angle is commonly affected by computer usage [ 17 ]. McEvoy and Grimmer (2006) reported that a decrease in this angle reflects a "poking-chin" posture [ 28 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…We undertook a systematic review of published research, which reported on sitting posture measurement tools. We identified nine relevant papers describing only three measurement approaches (goniometer [ 17 - 19 ], inclinometer [ 20 - 23 ] and flexicurve [ 24 , 25 ]). None of these approaches has been validated for adolescents (high school students).…”
Section: Introductionmentioning
confidence: 99%
“…The cervical range of motion was measured with a single-bubble inclinometer. 14 Chiropractic treatment included spinal manipulative therapy of the pelvis and the cervical and thoracic spine with Activator technique according to Activator protocol. The pelvis was adjusted to correct pelvic unleveling; and the thoracic spine was adjusted along with the cervical spine to address the point tenderness in the neck and shoulder region, as well as to help with any altered head position and to increase the MMO.…”
Section: Case Reportmentioning
confidence: 99%
“…M-test의 동작을 했을 때 양성 소견은 다음의 기준으로 13,14) . 경부 굴곡과 신전의 경우 두정 부와 첫째등뼈 가시돌기 위치에 각각 경사계를 위치하고 측정하여 흉부 움직임의 영향을 배제하였다 13) .…”
unclassified
“…경부 굴곡과 신전의 경우 두정 부와 첫째등뼈 가시돌기 위치에 각각 경사계를 위치하고 측정하여 흉부 움직임의 영향을 배제하였다 13) . 좌⋅우 측 굴, 좌⋅우 회전의 경우 두정부에 경사계를 위치하고 어 깨의 움직임을 제한한 상태로 측정하였다 14) . …”
unclassified